New Normal After Education Game Design Pandemic Uses Approaches Agile Scrum Application of Finite State Machine (FSM) Method - Tri Ferga Prasetyo; Ade Bastian; Lidya Tresna Wahyuni (IJISTECH (International Journal of Information System and Technology), 2021)
Game is an application that infers human behavior into software, and players who play the game feel they are entering the game world. Games can be used as a medium for information and education. The current rise of Covid-19 requires every individual to implement health protocols in their daily life. This term is called new normal. New normal is a change in behavior to continue carrying out normal activities but with the addition of implementing health protocols to prevent Covid-19 transmission. Unfortunately, in everyday life, the application of the new normal is less effective so that in one area, new cases have emerged and the PSBB must be re-applied. The new normal themed educational game can be a fun information medium for the community, with the New Normal After Pandemic educational game, it is hoped that it can educate the public in implementing health protocol rules. This game was created using Construct 2 software because it is based on HTML 5 which is specifically for 2D platforms. 2D designs are created using Corel Draw X7, Easy Paint Tools SAI and Adobe Photoshop. The final result of this study is a game application that applies the FSM (Finite State Machine) control system design method in each level rule and uses the Agile Scrum system development method with a process of 2x sprint iterations